ANALYSIS AND DETERMINATION OF HARD LAYERS USING GEOELECTRIC METHODS FOR THE BASIS OF CONSTRUCTION OF NEW BUILDINGS AT THE BENGKALIS STATE POLYTECHNIC - Alfauzan Yendra; Abdul Haris Salam (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
State Polytechnic of Bengkalis located on the Bengkalis island where the island of Bengkalis consists of a layer of peat. This layer of peat we know is a soft layer so it is dangerous if we build a building on this layer. State Polytechnic of Bengkalis at the moment is intense in the construction phase of the building in State Polytechnic of Bengkalis needs to be reviewed geotechnique as input for the new construction of buildings in the area of State Polytechnic of Bengkalis campus. This research uses the Geo Electrical survey uses Schlumberger configuration method to obtain subsurface resistivity data. From the measurement result of Geo Electrical survey uses Schlumberger configuration method 5 point of measurement in campus area of State Polytechnic of Bengkalis in can resistivity value for peat soil and soft soil is between 5 - 100 ohm with depth 0 m to depth 7 m. As for the hard layer has a resistivity above 100 ohm which is at a depth of 7 meters upwards. The result the authors suggest for the construction of new buildings in the campus area State Polytechnic of Bengkalis is to establish a foundation at a depth of 7 meters and above so that new buildings can be more solid